Admission pack for newly diagnosed diabetes: help or hindrance?. (24th May 2012) - Jefferies, K; Haest, J; Edge, J
Abstract : Aims: In order to improve communication and reduce insulin errors, a new admission pack was introduced in 2010 in a tertiary paediatric centre, for children newly diagnosed with diabetes. The aim of this study was to assess how well this pack is being used and what changes may improve it. We also asked for staff opinions about its use. Method: A retrospective study of all children aged 0-18 years presenting with newly diagnosed type 1 diabetes between June 2010 and April 2011. Notes were audited to establish which pages of the pack were being completed appropriately. Questionnaires were distributed amongst staff to determine their awareness of the pack, the sections they found most useful and changes they felt should be made. Results: 24 admissions were included. 66.7% of initial assessments and 70.8% of the nursing actions on admission were completed. Blood glucose (BG) charts were used in 96%, observation charts in 66.7% and food diaries in 45.8%. 75% of the history and examination sheets were used and the insulin dose calculation sheet was complete in 79.2%. Hypoglycaemia management was documented in only 29.2% of cases and the discharge checklist used in 25%. The dietitian section was completed in 45.8% of cases and the diabetes specialist nurse checklist in 79.2%. 19 staff with varying expertise received questionnaires. The majority of those who had completed the pack found the nursing checklist and care plan, BG chart, food diary, history sheets and insulin dose calculation particularly useful. However, awareness and completion of the pack differed amongst wards and staff. Of the general paediatricians, 4/5 had not completed it and 60% were unaware where to find copies. Conclusion: The admission pack has been introduced successfully and is highly rated by staff, although some parts are completed better than others. Staff awareness could be improved at MDT meetings and induction training. Alterations could also be made to ease its use but it provides a framework to ensure that management is safe and clear on the ward, discharge is planned, and it prevents duplication of patient information.